Função autonômica cardíaca e capacidade funcional em covid-19: contribuições para a confiabilidade da variabilidade de frequência cardíaca em hospitalizados e para a compreensão dos fatores que influenciam o desempenho funcional em casos leves - Araújo, Aldair Darlan Santos de (Universidade Federal de São Carlos, 2026)
Heart rate variability (HRV) and functional capacity are important markers of physiological status and cardiovascular system performance, with broad clinical and scientific applicability. The overall aim of this thesis was to test the intra- and inter-examiner reliability of HRV analysis in patients hospitalized with COVID-19, investigate cardiac autonomic modulation in individuals with mild COVID-19, and assess functional capacity in post-COVID-19 individuals with mild disease. In the first study, 103 patients hospitalized with COVID-19 were evaluated for the intra- and inter-examiner reliability of short-term HRV using linear and nonlinear indices. The analysis showed excellent reliability, with intraclass correlation coefficients (ICC) ranging from 0.956 to 0.999 and coefficients of variation below 10%, demonstrating that resting HRV measured by a portable device is highly precise, regardless of the examiner or timing of measurement. The second study investigated 130 individuals with mild COVID-19, stratified by time since infection (≤6 weeks, 2–6 months, and 7–12 months) and compared to a healthy control group. Groups with shorter time since diagnosis showed reduced parasympathetic modulation, while individuals assessed 7–12 months post-infection showed partial recovery compared to the control group. Multiple linear regressions indicated that age and time since infection were significant predictors of RMSSD and SD1, suggesting a transient effect of mild COVID-19 on the autonomic nervous system. In the third study, 115 post-COVID-19 individuals with mild disease were evaluated for functional capacity using the six-minute walk test (6MWT), cognitive function, cardiovascular responses, and determinants of functional performance. Participants assessed during the acute phase of infection (≤1 month) walked a significantly shorter distance than those assessed after three months, and depressive symptoms were also associated with reduced distance walked. No differences in cognitive function were observed among the groups, and factors such as age, BMI, sex, and anxiety did not significantly influence functional performance. Together, the results of this thesis provide robust evidence regarding HRV reliability in hospitalized patients, describe the gradual recovery of autonomic modulation following mild COVID-19, and identify factors associated with functional capacity, with important clinical implications for monitoring and rehabilitation of individuals affected by the virus.
Cardiac autonomic function and functional capacity in covid-19: contributions to the reliability of heart rate variability in hospitalized patients and to the understanding of factors influencing functional performance in mild cases
Keywords: Variabilidade da frequência cardíaca; Capacidade funcional; COVID-19; Confiabilidade de medida; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar; 4. Educação de Qualidade